Journeying Across Languages, Cultures, and Literatures: The Poetry of Mervyn Morris - Flajšarová, Pavlína (Hungarian Journal of English and American Studies, 2021)
The West Indian poet Mervyn Morris (1937-) is renowned for espousing the importance of a national language in creating national literature as well as for integrating European poetic heritage with Caribbean literary traditions. Through an exploration of Morris’s selected poems, the paper discusses the role language plays in shaping the themes of diasporic writing and of postcolonial identity, and argues that his works show a deep awareness of the fundamental aspects of West Indian and British culture. Since Morris “refuses to be trapped in the excesses of post-modern Romanticism or political propaganda parading as nationalism” (Thompson), the paper also looks at the presentation of eternal values like love and humanity celebrated in his poems. By foregrounding the frequent use of epiphanies in his poetry, Morris conveys human affection in the frame of colonial and postcolonial history. (PF)